Plasma-derived versus recombinant factor concentrates in PUPs: a never ending debate? - Berntorp, Erik (Hämostaseologie, 2017)
Inhibitor development in haemophilia is a serious complication to treatment with factor concentrates. Since the advent of more pure products, especially developed using recombinant DNA technology, some studies have shown an increased incidence of inhibitors in previously untreated patients (PUPs) receiving recombinant products whereas plasma-derived concentrates sometimes have been claimed to have a protective role, probably due to the content of von Willebrand factor (VWF). In fact, experiments indicate that the VWF may block uptake of factor VIII into macrophages for further processing to the immune system. Also, a competition between VWF and inhibitor binding to the C2 domain of factor VIII has been suggested. Recently, large cohort and surveillance studies have created a vigorous debate about the role of product class for inhibitor development as results have been conflicting. The only randomised prospective study, the SIPPET study, was published in 2016, and substantiated previous reports claiming that plasma derived concentrates give less inhibitors in patients with severe haemophilia A, previously not exposed to factor VIII. The debate will continue.
Keywords: haemophilia; inhibitor; factors concentrate; previously untreated patients